AGAMA AGEMING AJI: KEKAYAAN SPIRITUALITAS KEPERCAYAAN TERHADAP TUHAN YME DAN TANTANGAN PENERIMAANNYA - Akhol Firdaus (LP2M IAIN Tulungagung, 2020)
Abstract This article presents the spiritual wealth developing in the archipelago. Using a historical approach, the spiritual wealth of the archipelago, particularly in Java, is highlighted as part of the mystical culture of sentesis that has developed over thousands of years. That is what gave birth to the variety of spiritual expressions that have developed to this day in what is known as the local religion or the Believers in Java and the Archipelago. This article also presents a distortion of understanding of this spiritual wealth due to the colonialism project which was normally continued by the post-independence government. The article was submitted in a clustered discussion organized by the Directorate of Beliefs and Indigenous Peoples with the title